Endometrial Scratch Injury Induces Higher Pregnancy Rate for Women With Unexplained Infertility Undergoing IUI With Ovarian Stimulation: A Randomized Controlled Trial. (February 2016) - Maged, Ahmed M.; Al-Inany, Hesham; Salama, Khaled M.; Souidan, Ibrahim I.; Abo Ragab, Hesham M.; Elnassery, Noura
Objective: To explore the impact of endometrial scratch injury (ESI) on intrauterine insemination (IUI) success. Methods: One hundred and fifty four infertile women received 100 mg of oral clomiphene citrate for 5 days starting on day 3 of the menstrual cycle. Patients were randomized to 2 equal groups: Group C received IUI without ESI and group S had ESI. Successful pregnancy was confirmed by ultrasound. Results: 13, 21, and 10 women got pregnant after the first, second, and third IUI trials, respectively, with 28.6% cumulative pregnancy rate (PR). The cumulative PR was significantly higher in group S (39%) compared to group C (18.2%). The PR in group S was significantly higher compared to that in group C at the second and third trials. The PR was significantly higher in group S at the second trial compared to that reported in the same group at the first trial but nonsignificantly higher compared to that reported during the third trial, while in group C, the difference was nonsignificant. Eight pregnant women had first trimester abortion with 18.2% total abortion rate with nonsignificant difference between studied groups. Conclusion: The ESI significantly improves the outcome of IUI in women with unexplained infertility especially when conducted 1 month prior to IUI.